The Significance of the Graphic Mark: The New Medium of Nineteenth-Century Illustration in Conceptual and Pictorial Practice. (3rd April 2017) - Petersson, Sonya
Summary: This article aims at exploring the significance of the graphic with regard to the genre of illustration as a new medium in later nineteenth-century print culture, and thereby highlighting something that has often been treated as a transparent package of content: the graphic surface. The study accounts, on the one hand, for the graphic as a theme in nineteenth-century art theory and criticism, where it was recognized as a part of modernity and as the common denominator of print media widely conceived. On the other hand, it accounts for how graphic qualities in illustrations, such as the parallel strokes and cross-hatchings of the pictorial surface, functions as signs and partake in the meaning making process of illustrated literature, which has often been restricted to the analytical units of motif and story. In conclusion, the graphic logic that drives the study is demonstrated in the role of a media historical cut that questions the separation of 'the graphic arts' from print media in a broader sense and in the role of conducting an analysis of the graphicness of both text and picture where non-narrative signs are mediated into words, without evening out the differences between them.